Discovery techniques for calcitonin gene-related peptide receptor antagonists for potential antimigraine therapies - Labruijere, Sieneke; Ibrahimi, Khatera; Chan, Kayi Y; Maassenvandenbrink, Antoinette (Expert opinion on drug discovery, 2013)
Calcitonin gene-related peptide (CGRP) exerts a key function in migraine pathophysiology through the trigeminovascular system. Influencing this system via CGRP receptor antagonists seems to be an important new option in treating migraine attacks. To characterize new compounds, models are used to study the vascular effects as well as their effects on the central nervous system. The authors review the clinical trials and many different in vitro and in vivo experimental models that have been used to investigate the effects and side effects in animals, healthy subjects and patients. These experimental models are essential, not only in characterizing new CGRP receptor antagonists, but also in gaining more insight into the pathophysiological mechanisms behind migraines. Although triptans were a major breakthrough in migraine treatment, they are not effective for every patient and contraindicated in patients with cardiovascular disease. There is still a demand for other acute antimigraine acting drugs with CGRP receptor antagonists being the most promising candidates. CGRP plays a role in protection against ischemia, but CGRP receptor antagonists do not seem to affect this protection to a harmfull extent, when used incidentally as acute antimigraine treatment. In order for drug specificity to be increased, the site of action needs to be identified; this consequently may lead to a decrease in dosing with fewer side effects.